The Application of the PjBL Model Accompanied By E-LKPD Liveworksheet On Learning Outcomes In Islamic Cultural History - Siregar, Nurul Hidayah; Khadijah, Khadijah; Eliza, Rivdya; Marhamah, Marhamah; Sari, Milya; Batubara, Juliana (Prodi Pendidikan Keagamaan Islam, 2025)
This research is motivated by the low learning outcomes of students caused by subject matter that is too much and complex, making it difficult to understand. In addition, the motivation of students in participating in learning Islamic Cultural History (SKI) is also low, which can be seen from the summative exam scores that do not reach the Learning Objective Completeness Criteria (KKTP). The purpose of this study was to determine whether the learning outcomes of students who used the Project Based Learning (PjBL) model assisted by e-LKPD Liveworksheet were higher than the Direct Instruction (DI) model in SKI subjects in class XI MAN 1 Padangsidempuan in the 2024/2025 academic year. This research is a quantitative research with experimental method. The design used is quasi experimental design with posttest only control group design approach. The sampling technique used cluster random sampling, namely class XI MIA I as the control class and XI MIA V as the experimental class. Data collection techniques were carried out through tests and questionnaires. The results showed that the average score of the experimental class was 85.23, while the control class was 81.06. The results of hypothesis testing show that the t value of 2.43 is greater than t table 1.69, so it can be concluded that the PjBL model assisted by e-LKPD Liveworksheet has a significant effect on learning outcomes and student motivation in SKI subjects.